Computer modelling of coupled spaces: variations of eigenmodes frequency due to a change in coupling area - MEISSNER, Mirosław (Archives of Acoustics, 2009)
Acoustically coupled spaces have recently been drawing more and more attention in the architectural acoustics community, thus a determination of shapes and frequencies of eigenmodes in these room systems from computer-based models has become increasingly significant. In this investigation, an eigenvalue problem was solved numerically for a simple room system consisting of two connected rectangular spaces. In a numerical procedure, the forced oscillator method with a finite difference algorithm was applied. In order to determine the influence of irregularity of system shape on eigenmodes frequency, a modal behaviour in the coupled spaces was studied for several sizes of coupling area. Calculation results have shown that with the exception of a fundamental mode, the changes in resonant frequencies were relatively small. However, an increase in a system irregularity led to a coincidence of frequencies of neighbouring modes and variations in a sequence of modes on a frequency axis, which both contributed to a degeneration of eigenmodes.